Accessibility of service premises for people with disabilities in the historic areas of Lublin, Poland - Hołownia, Damian; Kozak, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
Agenda 2030 and its Sustainable Development Goals apply to all individuals, including those with disabilities. Currently, newly designed spaces and buildings in Poland meet accessibility requirements for people with disabilities. However, the situation differs in historic city centres and historic buildings. The aim of this study is to investigate the accessibility of service premises located in historic areas for people with mobility impairments. The UN Convention on the Rights of Persons with Disabilities identifies barriers as a key factor limiting the full participation of these individuals in social life, serving as the starting point for this research. The city of Lublin was selected as a case study. Methods included an analysis of the accessibility of service premises in terms of architectural barriers. Results were illustrated with photographs and expressed in percentages. The findings indicate that individuals with disabilities encounter significant difficulties in using the majority of gastronomic premises. Furthermore, the presence of numerous barriers in the historic city centres was noted, which hinders access for disabled tourists.